On perturbation of semi-Noether operators in incomplete spaces. I - Plaksa, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The perturbation problem is considered for a semi-Noether operator under minimal assumptions imposed on given spaces.